LIFE AND WORK OF PROFESSOR VLADIMIR DAVCHEV, PHD (Annual of the Faculty of Philosophy in Skopje, 2021)
We received the news of the sudden death of Dr. Vladimir Davchev, a full-time professor at the Institute for Gender Studies at the Faculty of Philosophy in Skopje, with disbelief and shock. Professor Davchev wasn’t merely our professor and a colleague, but our lifelong friend. For the students, he was a valued professor, who knew how to be friendly but also to impart knowledge. We didn’t lose just a man, but an individual with strong moral values, and as such he was virtuous, just, collegial, and moderate; a person whom you can collaborate with and also lean on.